Digital Advertising Trends and Effectiveness in the Modern Era: A Systematic Literature Review - Prihatiningsih, Titin; Panudju, Redi; Prasetyo, Iwan Joko (Manunggal Halim Jaya, 2025)
This research aims to understand the latest trends in digital advertising and measure the effectiveness of video content and social media in increasing engagement, conversion, brand awareness, and customer loyalty. This research utilizes a quantitative study design with a cross-sectional survey to collect data from social media-active consumers exposed to video advertisements. Data analysis used descriptive and inferential statistical techniques to test the relationship between these variables. The findings showed that video content is highly effective in attracting attention and maintaining consumer interest longer than text or static images. The video also allows for more complex and emotional messaging. Social media facilitates two-way interaction between brands and consumers, strengthening relationships and increasing customer loyalty. Integrating video content with social media platforms such as YouTube, Facebook, Instagram, and TikTok significantly increases engagement and conversion. Personalization of ads through artificial intelligence (AI) technology has also been shown to increase campaign relevance and effectiveness. This research contributes to the digital advertising literature by demonstrating the importance of integrating video and social media content and using AI technology for personalization. The findings offer practical guidance for advertisers to improve the effectiveness of their campaigns. However, this study has limitations in sample coverage and quantitative analysis focus. Future research should expand the sample and incorporate qualitative approaches to gain more comprehensive insights.